New records of moth flies (Diptera: Psychodidae) from Croatia, with the description of Berdeniella keroveci sp.nov. - Kvifte, Gunnar Mikalsen; Ivković, Marija; Klarić, Aleksandra (Zootaxa, 2013)
Berdeniella keroveci sp. nov. is described based on males collected in Croatia. Current knowledge of the psychodid fauna of Croatia is reviewed and new records of 16 species are presented. Short taxonomic notes on Pericoma pseudocalcilega Krek, 1972, Pneumia balkanica (Krek, 1990), Pneumia mutua (Eaton, 1893), Clogmia albipunctata (Williston, 1893) and Lepiseodina tristis (Meigen, 1810) are given. In total, 33 species of Psychodidae are known to occur in Croatia.